Lapidari 3: Images, Part II - Mazzi, Marco (punctum books, 2015)
In June and July 2014, philologist Vincent W.J. van Gerven Oei and photographer Marco Mazzi undertook the Albanian Lapidar Survey, a project to map, document, and photograph the large majority of Albanian lapidars, a particular type of monument, mainly produced in the period that the communist Labor Party of Albania ruled the country (1945-1990) to commemorate the partisan victims, battles, and military units from the National Anti-Fascist Liberation War (which coincided with World War II), as well as historical figures from before the liberation and the accomplishments of socialism in Albania afterward. These lapidars, which can still be found, albeit in ever decreasing numbers, all over the country - in cities and villages, alongside roads, in forests and on mountain passes - are witness to an enormous expenditure of labor and resources to turn the landscape into a site of what was called "monumental propaganda." The Albanian Lapidar Survey aimed to capture these monuments as fact. The results of this project are collected into a three-volume, dual-language (English and Albanian) catalogue, under the title Lapidari. The first volume comprises a series of critical reflections on Albanian monumentality of the period 1945-1990 from a variety of perspectives, as well as historical documents and a full indexation of all inscriptions found on the documented monuments. Volume 2 and Volume 3 feature the photographic documentation of all 649 recorded monumental sites by photographer Marco Mazzi.